Automated mineralogy and petrology - applications of TESCAN Integrated Mineral Analyzer (TIMA) - Hrstka,T.; Gottlieb,P.; Skala,R.; Breiter,K.; Motl,D. (Journal of Geosciences, 2018)
The collection of representative modal mineralogy data as well as textural and chemical information on statistically significant samples is becoming essential in many areas of Earth and material sciences. Automated Scanning Electron Microscopy (ASEM) systems provide an ideal solution for such tasks. This paper presents the methods and techniques used in the recently developed TESCAN Integrated Mineral Analyzer (TIMA-X) with Version 1.5 TIMA software. The benefits from the use of a fully integrated quantitative energy-dispersive X-ray spectrometry (EDS) and an advanced statistical approach to ASEM systems are demonstrated. Typically, the system can handle more than 500,000 X-ray events per second. Using a common spectral total of 1000 events this represents the acquisition of 500 spectra per second. A number of measurement modes is available to make the most effective use of these spectra depending on the application.For a back-scattered electrons (BSE) map combined with EDS data with spatial resolution of 10 µm, this represents the high-resolution measurement of c. 1 cm2 of a thin section or a polished rock surface in 30 minutes. A patented X-ray spectrum clustering algorithm that lowers the chemical detection limit is described and an example of its use is shown. The modal and textural (liberation, association, size etc.) data produced are statistically robust and provide information across a broad range of Earth and material sciences. A comparison with some other available instruments is also provided together with a number of case studies.
Keywords: TIMA; Automated SEM/EDS; applied mineralogy; modal analysis; artificial intelligence; neural networks